ALGORITMA C4.5 UNTUK PENENTUAN TIM PEMAIN UTAMA OLAHRAGA VOLI - Effendi, Rohmat Irvan; Remawati, Dwi; Fitriasih, Sri Hariyati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2023)
The current system in the DX JUNIOR Volleyball Team still uses a manual process, because there is no application or method used in determining players on the first team. However, with so many prospective players who want to play to become the main players, it becomes an obstacle in determining who deserves to enter the first team, and requires a long process in determining prospective players who are eligible and not eligible to enter the first team. So a determination classification system is needed by applying the C4.5 Algorithm method which can simplify the process of determining the main players. The purpose of this research is to create an application for Classification of Volleyball First Team Determination Using the C4.5 Algorithm in the DX JUNIOR volleyball team. The methods used include the type of data for data collection techniques using observation and interview methods and literature studies to determine the theoretical basis for research related to the matters under study. As for the system analysis method, for system design using UML, Matlab. The application of the C4.5 Algorithm method for determining first team players was made to make it easier to determine prospective players in the first team based on criteria, namely Physical Strength, Attitude, Cooperation, and Test Score. The results of the research were tested using the blackbox test the system runs accordingly, the validity test was tested on 72 data, resulting in an analysis value which can be concluded that the results of the comparison of Entropy and Gain calculated manually with Entropy and Gain calculated by the program process the results are the same, so the application is in accordance with the results of the C4.5 algorithm analysis.